A topology of DC electric springs for DC household applications. Issue 5 (1st May 2019) - Wang, Qingsong; Zha, Daojun; Deng, Fujin; Cheng, Ming; Buja, Giuseppe
Abstract : There are two types of existing direct current (DC) electric spring (DCES), of which the one realised by alternative current electric spring has low power density because of the low‐pass filter with big volume, another one is realised by DC/DC converters but too complicated. In this study, aiming at households' applications, a novel topology is proposed for DCES, using a three‐port DC/DC converter with a bi‐directional boost‐buck converter (BBC) paralleled at one port. Critical load (CL), noncritical load (NCL) and power source are located at separate port. Besides the isolation electrically, the most important advantage is that the NCL is no longer in series with DCES, which is possibly the first attempt to change the connection type of a visual NCL with an electric spring (ES) from series to normal parallel way. With the proposed DCES, CL power is regulated stable while the fluctuations are transferred to the NCL. Meanwhile, the DCES does not provide nor absorb active power at steady‐state. When the battery voltage reaches its lower or upper limits, the protection mechanism will start to ensure safe operations. The effectiveness of the proposed DCES topology and its control has been validated by simulation and experiment results.